2013
DOI: 10.1007/s00253-013-4983-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cell growth and starch production in the marine green microalga Tetraselmis subcordiformis under extracellular phosphorus-deprived and sequentially phosphorus-replete conditions

Abstract: Microalgal starch is a potential feedstock for biofuel production. Nutrient stress is widely used to stimulate starch accumulation in microalgae. Cell growth and starch accumulation in the marine green microalga Tetraselmis subcordiformis were evaluated under extracellular phosphorus deprivation with initial cell densities (ICD) of 1.5, 3.0, 6.0, and 9.0×10 6 cells mL were all obtained in the culture with the ICD of 3.0× 10 6 cells mL −1 . Appropriate ICD could be used to regulate the intracellular phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 46 publications
6
31
1
Order By: Relevance
“…In agreement with our findings, Dunaliella tertiolecta was reported to grow in a medium lacking P when the culture was started with P-replete cells [41]. A similar behavior was found in Tetraselmis subcordiformis since the intracellular accumulated P, sustained cell growth when extracellular P was absent [42]. T. subcordiformis is related to C. reinhardtii, and its high survival rate under P-deprivation can be explained by the mobilization of internal reserves of Pi from Poly-P molecules, the secretion of periplasmic phosphatases (which can cleave Pi from Pi esters in the immediate environment), the activation of high-affinity Pi uptake and the substitution of phospholipids for glycolipids and sulfolipids [43].…”
Section: A N U S C R I P Tsupporting
confidence: 91%
“…In agreement with our findings, Dunaliella tertiolecta was reported to grow in a medium lacking P when the culture was started with P-replete cells [41]. A similar behavior was found in Tetraselmis subcordiformis since the intracellular accumulated P, sustained cell growth when extracellular P was absent [42]. T. subcordiformis is related to C. reinhardtii, and its high survival rate under P-deprivation can be explained by the mobilization of internal reserves of Pi from Poly-P molecules, the secretion of periplasmic phosphatases (which can cleave Pi from Pi esters in the immediate environment), the activation of high-affinity Pi uptake and the substitution of phospholipids for glycolipids and sulfolipids [43].…”
Section: A N U S C R I P Tsupporting
confidence: 91%
“…4b). Similar phenomenon has also been reported by other researchers (Khozin-Goldberg and Cohen, 2006;Yao et al, 2013).…”
Section: The Variation Of Biochemical Compositionsupporting
confidence: 92%
“…These results indicated that in microalgal growth with intracellular phosphorus the algal density growth rate and the biomass growth rate was uncoupled to a certain extent. Similar phenomenon was observed by Yao et al (2013), Zhang and Hong (2014).…”
Section: The Variation Of Microalgal Growth Rate and Lipid/tag Contentsupporting
confidence: 87%
“…Phosphorus limitation in Chlorella vulgaris slowed dry weight increases and stopped cell division completely after 12 h of growth. The relative content of starch in phosphorus-starved cells (in % of DW) was lower than in sulfur-starved Chlorella vulgaris cells (Brányiková et al, 2011), similar to the marine alga Tetraselmis subcordiformis (Yao et al, 2013;Yao et al, 2012). (Wu et al, 2013).…”
Section: Phosphorusmentioning
confidence: 76%